Przestępstwo naruszenia autorskich praw osobistych z art. 115 ust. 3 Ustawy z dnia 4 lutego 1994 r. o prawie autorskim i prawach pokrewnych w świetle zasady określoności - Piesiewicz, Piotr F. (Studia Prawa Publicznego, 2019)
The Act of February 4, 1994 on Copyright and Related Rights, which regulates issues related to the protection of copyrights, belongs to the private law system (its provi- sions protect the private interest). However, the Act includes both administrative and criminal law provisions aimed at protecting the public interest. The literature rightly points out that the systemic division into public and private law is becoming increasingly less pronounced, due to the permeation of legal domains belonging to both systems. An example of such interpenetration are the provisions of copyright law. This statement is significant for the considerations made in this article due to the statutory method of penalising certain behaviour contained in the provisions of the Copyright and Related Rights Act. Criminal law provisions, systemically related to public law and protecting the public interest, contain references to the provisions of the Copyright and Related Rights Act regulating the scope of copyright protection, i.e. private law norms. In the context of the requirements that should be met by criminal law, such a reference raises doubts, which are particularly highlighted in Art. 115 para. 3 of the Copyright and Related Rights Act. This issue is impor- tant because the Constitutional Tribunal in its judgment of 17 February 2015, Ref. K 15/13 recognised this provision as constitutional. Therefore, he concluded that the principle of the specificity of a criminal act does not preclude the legislator from using terms that are imprecise or vague if their designations can be determined. At the same time, the Constitutional Tribunal has not presented any arguments indicating that in this case the determination of the designates of Art. 115 para. 3 of the Copyright and Related Rights Act does not cause any difficulties. The author of this article attempts to determine the extent of criminal liability in the event of a violation of author’s moral rights (Article 115 section 3 of the Copyright and Related Rights Act), at the same time indicating the difficulties that are associated with the unambiguous determination of behaviour which Art. 115 para. 3 of the Copyright and Related Rights Act penalises.